2006
DOI: 10.1097/01.mjt.0000155113.89092.58
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Parameters of Total and Unbound Valproic Acid and Their Relationships to Seizure Control in Epileptic Children

Abstract: The aims of this study were to define the relationship between total and unbound valproic acid (VPA) concentrations, to compare pharmacokinetic parameters of total and unbound VPA, and to determine the difference in pharmacokinetic parameters between the seizure-controlled and -uncontrolled groups. Total and unbound steady-state serum concentration of VPA were determined at trough and at 5 hours after the morning dose from 29 pediatric patients with epilepsy who were receiving valproic acid as monotherapy ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In addition, Panomvana Na Ayudhya et al reported that seizure uncontrolled paediatric patients had a significantly higher elimination rate constant (K e ) and a significantly shorter half-life of VPA. However, the sample size of this study was relatively small and future study with a larger sample size is required to confirm the results [51]. With regard to psychiatric patients, even though a therapeutic range for mood-stabilizing activity of VPA has not yet been published, several studies reported that a concentration of at least 50 mg l À1 might be required to achieve clinical response in WT, BMI, age, gender, co-medication (PNZ, THP, CZP, RPD, HPD, CPZ), VPA dose…”
Section: Discussionmentioning
confidence: 76%
“…In addition, Panomvana Na Ayudhya et al reported that seizure uncontrolled paediatric patients had a significantly higher elimination rate constant (K e ) and a significantly shorter half-life of VPA. However, the sample size of this study was relatively small and future study with a larger sample size is required to confirm the results [51]. With regard to psychiatric patients, even though a therapeutic range for mood-stabilizing activity of VPA has not yet been published, several studies reported that a concentration of at least 50 mg l À1 might be required to achieve clinical response in WT, BMI, age, gender, co-medication (PNZ, THP, CZP, RPD, HPD, CPZ), VPA dose…”
Section: Discussionmentioning
confidence: 76%
“…Valproate (VPA) is a short-chain fatty acid with HDAC inhibitor activity that is widely prescribed as one of the first-line medications for epilepsy and bipolar disorders [10], [11], [12], [13]. Chronic VPA treatment in bipolar patients often restricts the frequency of mood swings to either the manic or depressive state [14].…”
Section: Introductionmentioning
confidence: 99%
“…Both the elimination rate constant and volume of distribution of the unbound VPA are much higher than those of the total VPA; clearance was approximately 10-fold higher. The amount of VPA not bound to proteins is linearly dependent on the dose administered [83].…”
Section: Hdaci Pharmacokinetics Short Chain Fatty Acidsmentioning
confidence: 99%